Indian math olympiad questions are famous (infamous?) for being very analytical. There mostly do not exist any clever one line proofs. Multiple cases have to be analyzed and exhaustively eliminated before arriving upon the correct answer.

I tried solving problems from the Indian National Mathematics Olympiad, 2013 today. My solutions are different (lengthier, and hence perhaps instructive) from the official solutions given online. Hopefully they can be of help to anyone interested in mathematical problem solving.

The Indian National Mathematics Olympiad (INMO) is offered to those candidates who have cleared the Regional Mathematics Olympiad (RMO). The questions that are given are of a difficulty level comparable with P1, P4 of the International Math Olympiad.

I do plan on running a seminar on competitive math problem solving this summer. This is useful for all sorts of things, like getting better at algorithms, improving analytical skills in finance, etc. Please do let me know if you’d be interested in that sort of thing.

• Find all positive integers $m,n$ and primes $p\geq 5$, such that $m(4m^2+m+12)=3(p^n-1)$

First, we make a couple of observations. As $p^n-1$ is a multiple of $2$, $m$ will also have to be a multiple of $2$. This can be re-written as $4m^3+m^2+12m+3=3p^n$. On factorizing the left hand side, we get $(4m+1)(m^2+3)=3p^n$. Hence, as the right hand side is a multiple of $3$, either $4m+1$ is a multiple of $3$, or $m$ is a multiple of $3$.

If $4m+1$ is a multiple of $3$ and $m$ is not, then it has to be a multiple of $9$, as $m\equiv 2\pmod 3$ is the only possibility. This is impossible as $p\geq 5$. Hence, $3|m$. Note that from our previous observation, we also know that $2|m$. Hence, combining the two, we get $6|m$.

Let $m=6m'$. Then we have $(24m'+1)(12m'^2+1)=p^n$ (we obtain this after canceling out $3$ on both sides). For $m'\geq 2$, we have $24m'+1\leq 12m'^2+1$. Hence, as the right hand side is $p^n$, we have $24m'+1|12m'^2+1$. This implies that $24m'+1|12m'^2+1-(24m'+1)=12m'(m'-2)$. The right hand side is a multiple of $12m'$ while the left hand side is not. Hence, this is only possible if $m'-2=0$, or $m'=2$. As $m=6m'$, we get $m=12$.

From this, we can deduce that $(24m'+1)(12m'^2+1)=49^2$, and hence $p=7$ and $n=4$. $(12,7)$ is the only solution. QED

• Let $a,b,c,d$ be positive integers such that $a\geq b\geq c\geq d$. Prove that $x^4-ax^3-bx^2-cx-d$ has no integer solutions.

Let $x$ be a solution. Clearly $x=0$ cannot be a solution, as then we would have $d=0$, which is impossible as $d$ is a positive integer. Hence, let us assume that $x$ is a non-zero integer. Then we have $x^4-ax^3-bx^2-cx=d$. Therefore, $x|d$. Let $d'=\frac{d}{x}$. Then we have $x^3-ax^2-bx-c=d'$. Continuing like this, we get $x=a+b'+c''+d'''$, where $d'''=\frac{d}{x^3}$, $c''=\frac{c}{x^2}$, and $b'=\frac{b}{x^2}$.

In other words, we have $x=a+\frac{b+c'+d''}{a+b'+c''+d'''}$. Clearly, as $a\geq b\geq c\geq d$, we have $\frac{b+c'+d''}{a+b'+c''+d'''}\leq \frac{a+b'+c''}{a+b'+c''+d'''}<1$. Hence, $x$ is not an integer. Hence proved. QED

•  Let $n$ be a positive integer. Call a nonempty subset $S$ of $\{1,2,\dots,n\}$ good if the arithmetic mean of the elements of $S$ is also an integer. Further, let $t_n$ denote the number of good subsets of $\{1,2,\dots,n\}$. Prove that $t_n$ and $n$ are either both odd or even.

Clearly, this is equivalent to proving that $t_n-n$ is always even. Note that subsets consisting of one element have an arithmetic mean that is an integer. Hence, we can prove that the number of good subsets of $\{1,2,\dots,n\}$ containing at least two elements will be even. The way that we’ll prove this assertion is by forming a pairing between sets: if $\{a_1,\dots,a_k\}$ is one such subset, then consider the set $\{n+1-a_1,\dots,n+1-a_k\}$. Clearly this set will also have an integer average, and the map $i\to n+1-a$ is idempotent. Hence, the mapping is bijective.

Case 1: Let $n$ be even. The only cases in which bijective pairing maps a set to itself is for every $i$ in the set, $n+1-i$ is also included in it. As there is no $i\in\{1,2,\dots,n\}$ such that $i=n+1-i$, as $n+1$ is odd, a set for which bijective pairing fails will have to contain an even number of elements. Hence, $t_{2k+1}$ is even for all $k\geq 1$. For sets of the form $t_{2k}$, if $i$ and $n+1-i$ are both included, then the average will be $\frac{k(n+1)}{2k}$, which is clearly not an integer as $n+1$ is odd. Hence, every good set can be bijectively paired with a different good set, which implies that the total number of good sets is even.

Case 2: Let $n$ be odd. Let us study the good sets for which the map $i\to n+1-i$ does not produce a different set. The only different is that when $i=\frac{n+1}{2}$, $i=n+1-i$. Hence, sets of both odd and even number of elements can map to themselves through this pairing. However, if we can prove that $t_{odd}$ and $t_{even}$ are both odd, then their sum will be even. Combining this with the fact that the number of sets which map to other sets is anyway even, we get a total number of even sets.

Let us consider $t_{2k+1}$. Any set of this form will have to contain the element $\frac{n+1}{2}$. The total number of such sets is hence ${n-1\choose 1}+{n-1\choose 2}+\dots+{n-1\choose n-1}=2^{n-1}-1$, which is odd.

Let us now consider $t_{2k}$. Then the element $\frac{n+1}{2}$ cannot be contained in such a set. Hence, the total number of elements is ${n-1\choose 1}+\dots+{n-1\choose n-1}=2^{n-1}-1$, which is odd.

Adding both cases together, we get an even number of sets that map to themselves through this mapping.

Hence, the total number of sets is even, which proves our assertion. QED

•  Let $a,b,c,x,y,z$ be positive real numbers such that $a+b+c=x+y+z$ and $abc=xyz$. If $a, $x, and $a\leq x, then prove that $x=a,y=b$ and $z=c$.

This is one of my favorite problems. Without loss of generality, let $x-a\geq c-z$. Then keeping $a+b+c$ constant, bring $c\to z$ and $a\to a+(c-z)=a'$. This keeps $b$ unchanged, and hence $a'z\geq ac$ (as $(a+x)(c-x)\geq ac$), which implies $a'bz\geq abc$. Now keeping $z$ constant, bring $a'\to x$ and $b\to y$. This again implies that $xy\geq a'b$, which implies that $xyz\geq a'bz\geq abc$. Hence, $xyz\geq abc$ if any of these changes happens. Hence, as $abc=xyz$, none of these changes should happen, and $a=x,b=y$ and $c=z$. QED